2017
DOI: 10.1016/j.celrep.2017.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi-Anemia-Associated Mutations Destabilize RAD51 Filaments and Impair Replication Fork Protection

Abstract: Fanconi anemia (FA) is a genetic disorder characterized by a defect in DNA interstrand crosslink (ICL) repair, chromosomal instability, and a predisposition to cancer. Recently, two RAD51 mutations were reported to cause an FA-like phenotype. Despite the tight association of FA/HR proteins with replication fork (RF) stabilization during normal replication, it remains unknown how FA-associated RAD51 mutations affect replication beyond ICL lesions. Here, we report that these mutations fail to protect nascent DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
(40 reference statements)
3
46
0
Order By: Relevance
“…The BCDX2 complex is responsible for RAD51 recruitment or stabilisation at damage sites,20 37 38 whereas the CX3 complex acts downstream of RAD51 recruitment to damage sites associated with Holliday junction resolvase activity, possibly indicating its function of stabilising gene conversion tracts 20 38. DMC1 is a meiosis-specific recombinase,17 whereas RAD51 is essential for mitotic and meiotic recombination 18 19. This role is consistent with the association of an XRCC2 gene variant or other RAD51 paralogue variants with a high risk of cancer 39…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The BCDX2 complex is responsible for RAD51 recruitment or stabilisation at damage sites,20 37 38 whereas the CX3 complex acts downstream of RAD51 recruitment to damage sites associated with Holliday junction resolvase activity, possibly indicating its function of stabilising gene conversion tracts 20 38. DMC1 is a meiosis-specific recombinase,17 whereas RAD51 is essential for mitotic and meiotic recombination 18 19. This role is consistent with the association of an XRCC2 gene variant or other RAD51 paralogue variants with a high risk of cancer 39…”
Section: Discussionsupporting
confidence: 56%
“…Two RecA-related recombinases, namely, DMC1 and RAD51, participate in meiotic HR. DMC1 is a meiosis-specific recombinase,17 whereas RAD51 is involved in mitotic and meiotic HR 18 19. Five RAD51 paralogues, namely, RAD51B, RAD51C, RAD51D, XRCC2 and XRCC3, have been reported to play indispensable roles in RAD51-mediated HR,20 but the detailed mechanism of RAD51-HR in meiosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these studies suggest that RAD51 has two distinct functions during replication stress: a BRCA-independent function in promoting the initial step of reversed fork formation, as discussed above, and a BRCA-dependent function whereby BRCA proteins protect the already formed reversed forks from nucleolytic degradation by stabilizing the RAD51 filament on the regressed arm. In BRCA2-deficient cells, this second function is lost, leading to the nascent strand degradation phenotype observed with BRCA2 mutants unable to stabilize RAD51 on ssDNA (Schlacher et al, 2011), with RAD51 mutants that destabilize the RAD51 nucleofilament (Kolinjivadi et al, 2017; Mijic et al, 2017; Zadorozhny et al, 2017), or with small molecules that inhibit RAD51 DNA binding activity (Taglialatela et al, 2017) . …”
mentioning
confidence: 99%
“…It has been demonstrated that BRCA1, BRCA2 and RAD51 function together to protect stalled -and possibly reversed -DNA replication forks from degradation by the MRE11 nuclease (Hashimoto et al 2010;Schlacher et al 2011;Schlacher et al 2012;Mijic et al 2017). It has been shown that a stable RAD51 nucleoprotein filament is required to protect DNA from MRE11 (Kolinjivadi et al 2017;Zadorozhny et al 2017). The BRCA1 and BRCA2 factors likely act directly or indirectly to stabilize the RAD51 nucleoprotein filament.…”
Section: Role Of Recombination Proteins In Promoting the Stability Ofmentioning
confidence: 99%